2015
DOI: 10.1021/acsnano.5b00053
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanowire–Graphene Core–Shell Nanostructure for Highly Stable Transparent Conducting Electrodes

Abstract: A copper nanowire-graphene (CuNW-G) core-shell nanostructure was successfully synthesized using a low-temperature plasma-enhanced chemical vapor deposition process at temperatures as low as 400 °C for the first time. The CuNW-G core-shell nanostructure was systematically characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Raman, and X-ray photoelectron spectroscopy measurements. A transparent conducting electrode (TCE) based on the CuNW-G core-shell nanostructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(185 citation statements)
references
References 31 publications
(47 reference statements)
8
177
0
Order By: Relevance
“…Nowadays, several alternative transparent electrodes have been reported, such as carbon nanotubes [5,6], grapheme [7,8], doped ZnO conducting films [9,10], conducting polymes [11,12], metal materials [13,14], etc. Currently, Ag nanomaterial is regarded as one of the most appealing transparent electrodes due to its excellent conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several alternative transparent electrodes have been reported, such as carbon nanotubes [5,6], grapheme [7,8], doped ZnO conducting films [9,10], conducting polymes [11,12], metal materials [13,14], etc. Currently, Ag nanomaterial is regarded as one of the most appealing transparent electrodes due to its excellent conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that G-Cu exhibited higher chemical stability than Ag network due to the fact that the graphene can retard the metallic TCEs to some extent oxidation in erosion solution. 20,45,46 Fig . 3F shows the corresponding photograph before and aer deposition of PANI lm, indicating that PANI can be only deposited on G-CuS TCE while almost no PANI was observed on the other three TCEs.…”
Section: Physicochemical Properties Of Tcesmentioning
confidence: 99%
“…Thus, to solve these problems, a variety of reports have introduced stretchable and transparent electrodes with hybrid structures of CuNWs and other materials, such as carbon nanomaterials, conductive polymers, and metal-based materials [44,[47][48][49][50][51][52]. Graphene, a representative carbon nanomaterial, has high mechanical strength and thermal resistance and low water vapor and oxygen permeability [48][49][50]. Although graphene has high electron mobility, its carrier concentration is very low, and as such, it can hardly serve as a transparent electrode by itself.…”
Section: Cu Nanowiresmentioning
confidence: 99%
“…Ahn et al reported CuNWs encapsulated with graphene (i.e. CuNW-graphene core-shell structure) [49]. Using lowtemperature plasma-enhanced chemical vapor deposition (LT-PECVD), a CuNW-graphene core-shell nanostructure was obtained, as shown in Figure 2(f).…”
Section: Cu Nanowiresmentioning
confidence: 99%